(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Sustainable nutrient management with the combination of organic and chemical fertilizer amendment expects a key part in upgrading stevia yield without harming the environment and to build up the nutrient balance with increasing soil fertility. A pot experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh to study the combined effect of vermicompost (VC) and chemical fertilizer (CF) on the growth, leaf biomass yield and stevioside content of stevia in acid soil. Six combinations of VC and CF were applied following completely randomized design (CRD) with three replications. Results showed that VC along with different rates of CF exerted significant influence on the growth, leaf biomass yield and stevioside content of stevia and postharvest soil fertility. The highest values for most of the parameters were found from the plant receiving VC @ 7.5 t ha−1 along with 50% CF. About 578% higher leaf biomass yield was obtained from the treatment VC7.5+CF50 over control. Stevioside content was increased with the increasing levels of VC up to 7.5 t ha−1 along with 75% of CF and also with the advancement of growth period from 30 to 60 days after planting. The highest amount of stevioside (11.05%) was detected in the leaves of plant of the same treatment at harvest. Soil acidity was significantly decreased with the increased levels of VC and CF where as soil fertility in terms of organic matter and nutrient content was increased. Considering the overall performance, farmers may be advised to cultivate stevia in acid soil applying VC @ 7.5 t ha−1 along with 50% chemical fertilizer to boost up stevia production under the agroclimatic condition of the study area in the context of Bangladesh J. Bangladesh Agril. Univ. 16(1): 73-81, April 2018